2015
DOI: 10.14430/arctic4488
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential Foraging Areas for Bowhead Whales in Baffin Bay and Adjacent Waters

Abstract: ABSTRACT. The bowhead whale (Balaena mysticetus) is the Arctic's largest and most dependent predator on zooplankton; however, knowledge about its important foraging areas in Baffin Bay and adjacent waters is limited. Data on movement, horizontal velocity (ms Mots clés : alimentation; baleine boréale; Balaena mysticetus; télémesure satellitaire; SLTDR; baie de Baffin; changement climatique Traduit pour la revue Arctic par Nicole Giguère.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…For example, if predictions hold for each species, Antarctic minke whales (Balaenoptera bonaerensis) need to swim (Table 1). Indeed as predicted, inspection of dives referred to as 'shallow non-feeding dives' by Antarctic minke whales in another study appeared to occur at approximately 5 m depth [16], shallower than the depth threshold set for defining dives in many studies [37,[60][61][62]. If other whales also optimize their dive depths and this is not taken into account when setting dive definition thresholds, then it is possible that migratory dives may not be recorded by these devices and a biased picture of the depth ranges used by species could be produced.…”
Section: Discussionmentioning
confidence: 73%
“…For example, if predictions hold for each species, Antarctic minke whales (Balaenoptera bonaerensis) need to swim (Table 1). Indeed as predicted, inspection of dives referred to as 'shallow non-feeding dives' by Antarctic minke whales in another study appeared to occur at approximately 5 m depth [16], shallower than the depth threshold set for defining dives in many studies [37,[60][61][62]. If other whales also optimize their dive depths and this is not taken into account when setting dive definition thresholds, then it is possible that migratory dives may not be recorded by these devices and a biased picture of the depth ranges used by species could be produced.…”
Section: Discussionmentioning
confidence: 73%
“…Bowhead whales use a wide range of habitats, suggesting flexible use of foraging areas (Nielsen et al, 2015), and this species may be expanding its distribution, as suggested by its recent presence in the Northwest Passage (Heide-Jørgensen et al, 2011). Recent satellite-tracking studies (tagging in 2008 -10) showed that bowhead whales moved out of the Disko Bay area between late May and early June (Laidre and Heide-Jørgensen, 2012) and then followed the continental shelf off West Greenland northward towards the northern part of Baffin Bay (Nielsen et al, 2015). Those observations are in agreement with bowhead detections in 2014 at stations BB10 and BB6 in early and late June, but they do not explain the detections in April.…”
Section: Discussionmentioning
confidence: 99%
“…The predictability in culturally inherited migration patterns and in habitat selection among narwhal populations is certainly different from the two other Arctic cetaceans, the bowhead whale ( Balaena mysticetus ; cf. Nielsen et al ., 2015; Lydersen et al ., ) and belugas ( Delphinapterus leucas ; cf. Suydam et al ., ).…”
Section: Discussionmentioning
confidence: 99%